Exploring mechanisms of change in cognitive therapy and interpersonal psychotherapy for adult depression. (July 2017) - Lemmens, Lotte H.J.M.; Galindo-Garre, Francisca; Arntz, Arnoud; Peeters, Frenk; Hollon, Steven D.; DeRubeis, Robert J.; Huibers, Marcus J.H.
Abstract: The present study explored the temporal relationships between change in five candidate causal mechanisms and change in depressive symptoms in a randomized comparison of individual Cognitive Therapy (CT) and Interpersonal Psychotherapy (IPT) for adult depression. Furthermore, hypotheses concerning the mediation of change in these treatments were tested. Patients were 151 depressed adult outpatients treated with either CT ( n = 76) or IPT ( n = 75). Depression severity was assessed with the BDI-II. Candidate mediators included both therapy-specific as well as common factors. Measures were taken multiple times over the course of treatment (baseline, mid-, and post-treatment). Pearson's correlations and Latent-Difference-Score models were used to examine the direct and indirect relationships between (change in) the candidate mediators and (subsequent) (change in) depression. Patients showed improvement on all measures. No differential effects in pre- to post-treatment changes were observed between the two conditions. However, change in interpersonal functioning occurred more rapidly in IPT. Only little empirical support for the respective theoretical models of change in CT and IPT was found. Future studies should pay special attention to the timing of assessments and within-patient variance. Highlights: The mechanisms of change of CT and IPT for Depression are still largely unknown. We examined the temporal role of 5 candidate mechanisms in the context of an RCT. Over the course of treatment, patients showed improvement on all measures. No between-treatment differences were observed from pre-to post-treatment. We found only little support for the respective theoretical models of change.